Exploring Pilgrims’ Perceptions of Islamic Tour Operators in the United Kingdom: Insights for Improved Services - Ahmad, Shabir (The international journal of religious tourism and pilgrimage, 2024)
In recent years, religious tourism has gained popularity worldwide, with millions of people travelling to different destinations for religious purposes. The United Kingdom has a growing Muslim population, and Islamic religious tourism is no exception. However, little research has been conducted on the pilgrim’s perceptions of Islamic religious tour operators in the United Kingdom. Understanding these perceptions is essential for tour operators to provide better services and attract more customers. The present study aims to contribute to Islamic tourism research by assessing the perceptions of pilgrims toward religious tour operators in the United Kingdom. Employing a snowball sampling technique, this exploratory study surveyed 227 pilgrims who used the services of religious tour operators. The data were analysed in SPSS. The findings indicate that pilgrims in the United Kingdom generally hold a mixed perception towards religious tour operators offering religious journeys such as, Umrah, and Ziyara (pious visitation of sacred places). The pilgrims perceive these operators as profit-oriented enterprises that lack spiritual intentions which are not serving a noble cause. Most pilgrims expressed dissatisfaction with their services, although they are still preferred over government-sponsored schemes. The study provides insights for religious tour operators to improve their services and provide better experiences for pilgrims based on the identified factors in this study.